The experience of burnout among English language teachers in Iran: self and other determinants. Issue 5 (19th October 2016) - Sadeghi, Karim; Khezrlou, Sima
Abstract : Burnout in teachers is an important concern since it adversely impacts their instruction as well as their psychological, mental, and physical health. The present study examined the levels of burnout (i.e. emotional exhaustion, depersonalization, and reduced personal accomplishment) experienced by Iranian English language teachers. Specifically, the relationships of participants' gender, workplace context, grade level taught, and teaching experience to their burnout were investigated. Data were collected from 40 teachers using the Maslach Burnout Inventory. Overall, findings revealed that English teachers ( N  = 40) were experiencing high levels of reduced personal accomplishment ( M  = 18.72) and emotional exhaustion ( M  = 17.80). Results of one-way ANOVA showed significant differences among English language teachers with respect to burnout subscales. Significant correlations were found between burnout, workplace context, and grade level taught. A number of helpful suggestions for programs and individuals involved in relieving stress and burnout among teachers are presented.